Gastroenteritis in young children - D.F. Wittenberg (South African Family Practice)
Acute diarrhoea is due to intestinal infection. The patient ingests the pathogen which has contaminated water, food, drink, toys or anything that can be placed in the mouth. An inadequate and unsafe water supply, and poor application and practice of hygiene leads to faecal contamination. The most important complication is dehydration, with a poor correlation between the clinical features and actual dehydration. The management of the dehydrated patient depends on a careful assessment of the state of the circulation and the need for resuscitation. In most instances, oral rehydration is appropriate and fully effective if the solution is offered in small quantities at a time. Normally nourished infants do not require modification of their feeds beyond adapting the quantity offered as tolerated, but if diarrhoea persists, there is a risk of intestinal mucosal damage with malabsorption and nutritional consequences.